(untitled) (Research, Society and Development, 2020)
The training paths of higher education teachers to become teachers cross different paths in the teaching of the third degree, whether with the trajectories experienced in education courses or in their specific areas of activity. This study aimed to understand the training of university professors who work in undergraduate courses in Pedagogy, Chemistry and Biological Sciences at a Higher Education Institution in the State of Ceará. This research has a mixed quali-quanti approach. The main methodological theoretical foundations were the studies of specialists in the field of Education. We conclude that the initial training of the baccalaureate teachers is constituted as a training focused on specific areas linked to the initial training of each one, having no training of a pedagogical character for the exercise of teaching, however, because they have training at a specialization level, master’s degree and / or doctorate these professionals are able to teach in higher education.